Final answer:
An expression with at least three unlike terms can be simplified by combining like terms. For example, the expression 3x + 2y - 5z contains three unlike terms: 3x, 2y, and -5z. To simplify it, you can substitute values for the variables and perform the necessary operations.
Step-by-step explanation:
To write an expression with at least three unlike terms, you can use variables and constants. For example, the expression 3x + 2y - 5z contains three unlike terms: 3x, 2y, and -5z. To simplify this expression, you can combine like terms by adding or subtracting them. For instance, if x = 2, y = 4, and z = 1, then the simplified expression would be 3(2) + 2(4) - 5(1) = 6 + 8 - 5 = 9.